Multidisciplinary approaches to combat emerging viruses: diagnostics, therapeutic gene and vaccine delivery, and nanotherapeutics - Yu, Xianqiang; He, Qing; Kong, Qingming (Frontiers in Microbiology, 2024)
Emerging viruses, such as filoviruses (Ebola, Marburg), SARS and MERS coronaviruses, and Zika, pose significant threats to global public health, particularly for individuals with co-morbidities. To address these challenges, this review article explores multidisciplinary strategies for combatting emerging viruses. We emphasize the importance of developing accurate diagnostics, innovative therapeutic gene and vaccine delivery systems, and long-acting nanotherapeutics. These approaches are designed to enhance the safety and efficacy of treatments against these deadly pathogens. We discuss the collaborative efforts of virologists, geneticists, formulation scientists, clinicians, immunologists, and medicinal chemists in advancing these therapeutic modalities.